Biocompatible microemulsions based on limonene formulation, structure, and applications - Papadimitriou, Vassiliki (Langmuir : the ACS journal of surfaces and colloids, 2008)
The preparation of biocompatible (w/o) microemulsions based on R-(+)-limonene, water, and a mixture of lecithin and either 1-propanol or 1,2-propanediol as emulsifiers was considered. The choice of the compositions of the microemulsions used was based on the pseudo-ternary phase diagrams of the four-component system determined at 30 degrees C for different weight ratios of the components. When 1-propanol was considered as co-surfactant, the area of the microemulsion zone was remarkably increased. Interfacial properties and the dynamic structure of the emulsifier's monolayer were studied by electron paramagnetic resonance (EPR) spectroscopy using the spin-labeling technique. The rigidity and polarity of the interface were affected by the nature of the alcohol used as co-surfactant. When 1-propanol was used, the emulsifier's interface was much more flexible, indicating a less tight packing of lecithin molecules than in the case of 1,2-propanediol. In addition, the membrane's polarity was decreased when the diol was added as co-surfactant in the microemulsion system. To evaluate the size of the dispersed aqueous domains as a function of water content and other additives concentration, dynamic light scattering (DLS) measurements were carried out. Radii in the range from 60 to 180 nm were observed when 1-propanol was used as co-surfactant, and the water content varied from 0 to 12% w/w. Electrical conductivity measurements of R-(+)-limonene/lecithin/1-propanol/water microemulsions with increasing weight fractions of water indicated the appearance of a percolation threshold at water content above 4% w/w. Lipase from Rhizomucor miehei was solubilized in the aqueous domains of the biocompatible microemulsions, and the esterification of octanoic, dodecanoic, and hexadecanoic acids with the short-chained alcohols used as co-surfactants for the formulation of microemulsions was studied. The enzyme efficiency was affected by the chain length of the carboxylic acids and the nature of the alcohol. In the case of 1-propanol, a preference for the long-chain carboxylic acids was observed. On the contrary, when 1,2-propanediol was used formulation of the corresponding esters was not observed. This behavior could be possibly attributed to either the specificity of the lipase toward the alcohol employed for the esterification of the acids or the structural changes induced in the system when 1-propanol was replaced by 1,2-propanediol